Screening for inherited metabolic diseases using gas chromatography–tandem mass spectrometry (GC–MS/MS) in Sichuan, China. (1st November 2016) - Wang, Hong; Wang, Xia; Li, Yingying; Dai, Wei; Jiang, Dongmei; Zhang, Xiaodong; Cui, Yali
Abstract: The aim of this study was to retrospectively diagnose and confirm inherited metabolic diseases (IMD), from a small population of IMD high‐risk patients, with the aid of gas chromatography–tandem mass spectrometry (GC–MS/MS), technologies yet to be popularized in Sichuan, China. Using GC–MS/MS coupled with clinical diagnosis, we retrospectively analyzed samples of dried blood spots and urine specimen from 183 IMD high‐risk infant patients, who visited the West China Second Hospital of Sichuan University between June 2013 and October 2015. Four out of 183 IMD high‐risk infant patients were finally diagnosed to be IMD positive, among which two patients were identified with phenylketonuria, one with maple syrup urine disease, and 1 with methylmalonic academia. Restrictive diets and other symptomatic treatments were employed to treat the confirmed infant patients whose conditions are still under tracking and there are zero cases of death so far. GC–MS/MS was found to be an efficient and reliable way to detect IMD. It is necessary to apply GC–MS/MS, in addition to other clinical approaches, for diagnosing candidate IMD patients so that the confirmed patients can get medical intervention and timely treatment.